First description of the male of Sason sechellanum Simon, 1898 (Araneae: Barychelidae) - Marusik, Yuri M.; Gerlach, Justin (Zootaxa, 2011)
Barychelidae is a pantropical mygalomorph family with 44 genera and 303 species (Platnick 2010). Sason Simon, 1887 is a genus of average-sized spiders with nine species distributed from Seychelles to Ponape, Palau Islands and eastern Australia (Raven 1986; Platnick 2010). Five species of this genus are known from two sexes, two species are known only from females, one species is known only from the male, and one species is known only from a juvenile specimen. All species, except for S. robustum (O.P.-Cambridge, 1883), inhabit places not very far from seashore and have very limited distribution.